Two-dimensional ultrathin porous carbon nanosheet, preparation method thereof and supercapacitor

By preparing two-dimensional ultra-thin porous carbon nanosheets, the problem of insufficient energy density and power density in existing carbon materials in supercapacitors is solved, high specific surface area and capacitance are achieved, and cycling and electrochemical stability is improved. Improves the overall performance of the supercapacitor.

CN119480463APending Publication Date: 2025-02-18ZHONGTIAN ENERGY STORAGE TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411689371.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing carbon materials have problems in supercapacitors with insufficient energy density and power density, complex processing technology, low yield, poor cycle stability and electrochemical stability.

Method used

A method for preparing two-dimensional ultra-thin porous carbon nanosheets is adopted. By mixing Zn(NO3)2·6H2O or Co(NO3)2·6H2O with 2-methylimidazole, a precursor is obtained and under an inert atmosphere Annealing with molten salt to form two-dimensional ultra-thin porous carbon nanosheets with high specific surface area and conductivity.

Benefits of technology

It significantly improves the specific surface area and capacitance of carbon materials, improves cyclic stability and electrochemical stability, improves the energy density, power density and energy storage efficiency of supercapacitors, and extends the cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480463A_ABST
    Figure CN119480463A_ABST
Patent Text Reader

Abstract

The invention provides a two-dimensional ultrathin porous carbon nanosheet, a preparation method thereof and a supercapacitor. The method comprises the following steps: (1) mixing Zn (NO3) 2.6 H2O or a mixture of Co (NO3) 2.6 H2O and Zn (NO3) 2.6 H2O with 2-methylimidazole for reaction to obtain a precursor; and (2) the precursor and fused salt are mixed and then annealed under inert atmosphere protection, the two-dimensional ultrathin porous carbon nanosheet is obtained, the fused salt comprises first fused salt and second fused salt, the first fused salt comprises at least one of KCl and KNO3, and the second fused salt comprises at least one of LiCl, NaCl, ZnCl2 and LiNO3. The two-dimensional ultrathin porous carbon nanosheet prepared by the method has relatively high specific surface area and capacitance, relatively good cycling stability and electrochemical stability, and can maintain long-time stable capacitance performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of superconducting materials, and in particular to a two-dimensional ultra-thin porous carbon nanosheet and a preparation method thereof, and a supercapacitor. Background Art

[0002] Under the current severe environmental situation, the research and application of energy storage and conversion technology has become the focus of people's attention. As a highly efficient energy storage and conversion device, supercapacitors have the advantages of high energy density, high power density, and long cycle life. They are widely used in electric vehicles, wearable devices, smart homes and other fields. However, the energy density and power density of commercial supercapacitors still need to be improved.

[0003] As a necessary material for supercapacitors, the properties of carbon materials directly affect the performance of supercapacitors. Porous carbon is considered to be one of the excellent materials for manufacturing supercapacitors due to its low cost, stability and good conductivity. However, on the one hand, porous carbon still faces the disadvantages of complex processing technology, low yield and long processing time; on the other hand, the pore size and specific surface area of ​​existing biomass carbon are relatively low, and simple biomass carbon alone cannot provide suitable element doping, resulting in its low conductivity and specific capacity. Therefore, the existing carbon materials need to be improved. Summary of the invention

[0004] The present invention aims to solve one of the technical problems in the prior art at least to a certain extent. To this end, one object of the present invention is to provide a two-dimensional ultrathin porous carbon nanosheet and a preparation method thereof and a supercapacitor.

[0005] In a first aspect of the present invention, the present invention provides a method for preparing a two-dimensional ultrathin porous carbon nanosheet. According to an embodiment of the present invention, the method comprises: (1) Zn(NO3)2·6H2O or a mixture of Co(NO3)2·6H2O and Zn(NO3)2·6H2O is mixed with 2-methylimidazole to react to obtain a precursor; (2) After mixing the precursor with a molten salt, annealing the mixture under an inert atmosphere to obtain a two-dimensional ultrathin porous carbon nanosheet, wherein the molten salt comprises a first molten salt and a second molten salt, wherein the first molten salt comprises at least one of KCl and KNO3, and the second molten salt comprises at least one of LiCl, NaCl, ZnCl2, and LiNO3.

[0006] According to the method for preparing a two-dimensional ultrathin porous carbon nanosheet according to the above embodiment of the present invention, first, a mixture of Zn(NO3)2·6H2O or Co(NO3)2·6H2O and Zn(NO3)2·6H2O is mixed with 2-methylimidazole for reaction to obtain a precursor. The above precursor is used as a carbon source, which includes Co, Zn atoms and N atoms, and can form a metal / nitrogen co-doped carbon-based material, which has a high specific surface area, high electrical conductivity and good chemical stability. Then, the precursor is mixed with a molten salt and annealed under the protection of an inert atmosphere to obtain a two-dimensional ultrathin porous carbon nanosheet, and the molten salt includes a first molten salt and a second molten salt. The above precursor nanocrystals are used as nitrogen sources, carbon sources and metal sources, and carbonization is carried out in a molten salt high-temperature liquid environment. During the carbonization process, potassium ions enter the cavity structure formed by carbonization, prompting the rearrangement of the internal structural units, and converting the two-dimensional structure of the carbon material into a two-dimensional ultrathin nanosheet structure. On the other hand, the pore structure of the carbon material is changed by the etching effect of ion clusters (Cl ions, NO3 ions) in the molten salt. The changes in the two-dimensional ultra-thin nanosheet structure and pore structure can significantly increase the specific surface area and capacitance of the carbon material, making the catalytic sites inside the carbon material more evenly distributed, thereby achieving high energy density and power density, thereby improving the energy storage efficiency and output performance of the capacitor, and the porous carbon nanosheet has excellent cycle stability and electrochemical stability, thereby extending the cycle life of the supercapacitor.

[0007] As an example, Zn(NO3)2·6H2O is mixed with 2-methylimidazole to react to obtain a Zn-ZIF-L precursor. In the subsequent annealing and carbonization process, the Zn element volatilizes and forms defects inside the carbon material, thereby increasing the active sites of the carbon material and further improving the electrochemical performance of the carbon material.

[0008] As an example, a mixture of Co(NO3)2·6H2O and Zn(NO3)2·6H2O was reacted with 2-methylimidazole to obtain a Co-Zn-ZIF-L precursor. After the precursor was mixed with molten salt and annealed under the protection of an inert atmosphere, the volatilization of zinc further increased the specific surface area of ​​the carbon material. Under the combined action of zinc and cobalt, the internal catalytic sites of the carbon material were more evenly distributed, and the prepared carbon nanosheets had excellent electrochemical properties.

[0009] In some embodiments of the present invention, in step (1), the temperature at which the mixing reaction occurs is room temperature.

[0010] In some embodiments of the present invention, in step (1), the ratio of the mass of Zn(NO3)2·6H2O or the total mass of Co(NO3)2·6H2O and Zn(NO3)2·6H2O to the mass of 2-methylimidazole is independently (0.4-0.5):1. The inventors have found that controlling the mass ratio within the above range can ensure the stability of the quality of the synthesized product, reduce uncontrollable factors in the preparation process, and effectively control the morphology of the precursor.

[0011] In some embodiments of the present invention, in step (2), the mass ratio of the precursor to the molten salt is 1:(10-20). The inventors have found that controlling the mass ratio of the precursor to the molten salt within the above range can increase the specific surface area and capacitance of the two-dimensional ultrathin porous carbon nanosheets.

[0012] In some embodiments of the present invention, in step (2), the mass ratio of the first molten salt to the second molten salt is (5-8): (2-5). The inventors have found that when the mass ratio of the first molten salt to the second molten salt is within the above range, the molten salt has a lower melting point, which helps the molten salt system to operate at a lower temperature and save energy.

[0013] In some embodiments of the present invention, in step (2), the annealing temperature is 700°C to 900°C. For example, the annealing temperature is 700°C, 750°C, 800°C, 850°C, 900°C, etc. The inventors have found that controlling the annealing temperature within the above range can better maintain the properties and stability of the molten salt. The temperature range of 700 to 900°C is generally considered to be a more suitable temperature range in the molten salt system, which is beneficial to improving the electrochemical properties of the material.

[0014] In the second aspect of the present invention, the present invention proposes a two-dimensional ultra-thin porous carbon nanosheet. According to an embodiment of the present invention, the two-dimensional ultra-thin porous carbon nanosheet is prepared by the above method. As a result, the two-dimensional ultra-thin porous carbon nanosheet has a high specific surface area and capacitance, good cycle stability and electrochemical stability, and can maintain stable capacitance performance for a long time. It should be noted that the features and advantages described above for the method for preparing a two-dimensional ultra-thin porous carbon nanosheet are also applicable to the two-dimensional ultra-thin porous carbon nanosheet, which will not be repeated here.

[0015] In some embodiments of the present invention, the specific surface area of ​​the two-dimensional ultrathin porous carbon nanosheet is 1200-2500 m 2 / g, preferably 2000~2500m 2 / g, the pore size of the two-dimensional ultrathin porous carbon nanosheet is 0.5nm~3nm. For example, the specific surface area of ​​the two-dimensional ultrathin porous carbon nanosheet is 1200 m 2 / g,1500 m 2 / g,1800 m2 / g,2000 m 2 / g,2500 m 2 / g, etc., and the pore size is 0.5 nm, 1 nm, 2 nm, 3 nm, etc.

[0016] In some embodiments of the present invention, the thickness of the two-dimensional ultrathin porous carbon nanosheet is 1 nm to 6 nm.

[0017] In a third aspect of the present invention, a supercapacitor is provided. According to an embodiment of the present invention, the supercapacitor comprises the above-mentioned two-dimensional ultrathin porous carbon nanosheet. As a result, the supercapacitor has higher energy density and power density, thus having excellent energy storage efficiency and output performance, and having a longer cycle life.

[0018] The present invention has at least the following technical effects: (1) Two-dimensional ultrathin porous carbon nanosheets have high specific surface area and capacitance, good cycle stability and electrochemical stability, and can maintain stable capacitance performance for a long time.

[0019] (2) The two-dimensional ultra-thin porous carbon nanosheet has good environmental performance and renewability, which helps to reduce dependence on traditional non-renewable resources and promote the development of green energy. Compared with the existing technology, the two-dimensional ultra-thin porous carbon nanosheet of this application has important technical advantages in improving energy density, cycle life and environmental protection, which helps to promote the innovation and development of energy storage technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0021] Figure 1 CV graphs of the capacitors of Examples 1-2 of the present invention and Comparative Example 1 at different scan rates; Figure 2 1 is a GCD performance diagram of the capacitors of Examples 1-2 of the present invention and Comparative Example 1 at different current densities; Figure 3 is a graph of specific capacitance values ​​of capacitors under different current densities of Examples 1-2 of the present invention and Comparative Example 1; Figure 4 The capacitors of Examples 1-2 and Comparative Example 1 are 5 A g -1 Long cycle curves at different current densities. DETAILED DESCRIPTION

[0022] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.

[0023] Example 1 The preparation process of the two-dimensional ultrathin porous carbon nanosheet of Example 1 is as follows: (1) Dissolve 255 mg of Zn(NO3)2·6H2O and 583 mg of 2-methylimidazole in 20 mL of deionized water, respectively. Then, the two aqueous solutions were mixed rapidly and then stirred vigorously for 2 h. The resulting purple precipitate was kept undisturbed for another 12 h. The product was collected by centrifugation at 8000 rpm for 10 min, then washed with water and ethanol, and dried in an oven at 60 °C overnight to obtain Zn-ZIF-L precursor crystals.

[0024] (2) 1 g of the above Zn-ZIF-L precursor crystals was mixed with 5.5 g of KCl and 4.5 g of NaCl, and the mixture was ground in an agate mortar for more than 2 hours, and then the ground mixture was pyrolyzed in a furnace under a nitrogen atmosphere. Then, the mixture was heated to a final calcination temperature of 800 °C at a heating rate of 2 °C / min and maintained for 2 hours. The obtained product was taken out of the tube furnace and washed with 0.5 M HCl solution to remove impurities, rinsed with deionized water and ethanol several times, and freeze-dried to obtain a two-dimensional ultrathin porous carbon nanosheet. The specific surface area of ​​the two-dimensional ultrathin porous carbon nanosheet was 1209-1421 m 2 / g, pore diameter is 0.78-1.1 nm, and thickness is 3-6 nm.

[0025] The preparation process of supercapacitor is as follows: The nickel foam was cut into 2 cm × 1 cm rectangles, ultrasonically washed with ethanol and deionized water for 15 min, and dried at 50 ° C for 12 h. 8 mg of the above-prepared two-dimensional ultrathin porous carbon nanosheet Zn-NC, 1 mg of acetylene carbon black and 1 mg of PVDF were weighed and fully ground and mixed, and 10 ml of anhydrous ethanol was added and ultrasonically dispersed to obtain a slurry. The slurry was evenly coated on the nickel foam current collector, and the loading was kept at 2.0 mg / cm 2 , and dried at 80 °C for 12 h to obtain the Zn-NC electrode.

[0026] Example 2 The preparation process of the two-dimensional ultrathin porous carbon nanosheet of Example 1 is as follows: (1) Dissolve 120 mg of Co(NO3)2·6H2O, 135 mg of Zn(NO3)2·6H2O, and 583 mg of 2-methylimidazole in 20 mL of deionized water, respectively. The two aqueous solutions were then mixed rapidly and then stirred vigorously for 2 h. The resulting purple precipitate was kept undisturbed for another 12 h. The product was collected by centrifugation at 8000 rpm for 10 min, then washed with water and ethanol, and dried in an oven at 60 °C overnight to obtain Co-Zn-ZIF-L precursor crystals.

[0027] (2) 1 g of the above Co-Zn-ZIF-L precursor crystal was mixed with 5.5 g of KCl and 4.5 g of NaCl, and the mixture was ground in an agate mortar for more than 2 hours, and then the ground mixture was pyrolyzed in a furnace under a nitrogen atmosphere. Then, the mixture was heated to a final calcination temperature of 800 °C at a heating rate of 2 °C / min and maintained for 2 hours. The obtained product was taken out of the tube furnace and washed with 0.5 M HCl solution to remove impurities, rinsed with deionized water and ethanol several times, and freeze-dried to obtain a two-dimensional ultrathin porous carbon nanosheet. The specific surface area of ​​the two-dimensional ultrathin porous carbon nanosheet is 2170-2400 m 2 / g, pore diameter is 1.2-2.6 nm, and thickness is 1-3 nm.

[0028] The preparation process of supercapacitor is as follows: The nickel foam was cut into 2 cm × 1 cm rectangles, ultrasonically washed with ethanol and deionized water for 15 min, and dried at 50 ° C for 12 h. 8 mg of the above-prepared two-dimensional ultrathin porous carbon nanosheet Co-Zn-NC, 1 mg of acetylene carbon black and 1 mg of PVDF were weighed and fully ground and mixed, and 10 ml of anhydrous ethanol was added and ultrasonically dispersed to obtain a slurry. The slurry was evenly coated on the nickel foam current collector, and the loading was kept at 2.0 mg / cm 2 , and dried at 80 °C for 12 h to obtain the Co-Zn-NC electrode.

[0029] Comparative Example 1 (1) 255 mg of Co(NO3)2·6H2O and 583 mg of 2-methylimidazole were dissolved in 20 mL of deionized water, respectively. The two aqueous solutions were then mixed rapidly and then stirred vigorously for 2 h. The resulting purple precipitate was kept undisturbed for another 12 h. The product was collected by centrifugation at 8000 rpm for 10 min, then washed with water and ethanol, and dried in an oven at 60 °C overnight to obtain Co-ZIF-L precursor crystals.

[0030] (2) 1 g of the above Co-ZIF-L precursor crystals was mixed with 5.5 g of KCl and 4.5 g of NaCl, and the mixture was ground in an agate mortar for more than 2 h, and then the ground mixture was pyrolyzed in a furnace under a nitrogen atmosphere. Then, the mixture was heated to a final calcination temperature of 800 °C at a heating rate of 2 °C / min and maintained for 2 h. The obtained product was taken out of the tube furnace and washed with 0.5 M HCl solution to remove impurities, rinsed with deionized water and ethanol several times, and freeze-dried to obtain a two-dimensional ultrathin porous carbon nanosheet. The specific surface area of ​​the two-dimensional ultrathin porous carbon nanosheet was 1100-1200 m 2 / g, pore diameter is 4nm~6nm, and thickness is 3~5 nm.

[0031] (3) Preparation of supercapacitors: The nickel foam was cut into 2 cm × 1 cm rectangles, ultrasonically washed with ethanol and deionized water for 15 min, and dried at 50 ° C for 12 h. 8 mg Co-NC, 1 mg acetylene carbon black and 1 mg PVDF were weighed and mixed, and then 10 ml of anhydrous ethanol was added and ultrasonically dispersed. The slurry was evenly coated on the nickel foam current collector, and the loading was kept at 2.0 mg / cm 2 , and dried at 80 °C for 12 h to obtain the Co-NC electrode.

[0032] The performance of the capacitors prepared in Examples 1-2 and Comparative Example 1 was measured, as follows: The CV graphs of the capacitors of Examples 1-2 and Comparative Example 1 at different scan rates are shown in FIG. Figure 1 As shown, from Figure 1 As the scan rate increases from 10 mV s -1 Increase to 100 mV s -1 , the peak current density will also increase accordingly, and the CV curve still maintains the same shape, which shows that the Co-Zn-NC electrode of Example 2 is higher than that of Example 1 and Comparative Example 1, and has good cycle performance and is highly reversible.

[0033] The GCD performance diagrams and specific capacitance values ​​of the capacitors of Examples 1-2 and Comparative Example 1 at different current densities are shown in FIG. Figure 2 and Figure 3 As shown, from Figure 2 , 3 It can be seen that the current density is 1, 2, 5 and 10 A g -1 When the specific capacities of Example 1 are 101.67, 93.78, 64.5 and 44.4 F g -1 The specific capacities of Example 2 are 148.6, 131.1, 101 and 70.2 F g respectively.-1 The specific capacities of comparative example 1 are 86.2, 76.1, 52.2, and 34.3 F g, respectively. -1 .

[0034] The capacitors of Examples 1-2 and Comparative Example 1 were -1 The long cycle curve under current density is as follows Figure 4 As shown, from Figure 4 It can be seen that at 5 A g -1 The electrodes were subjected to charge-discharge cycle tests for 3000 times at a current density of 1.5 Å. After 3000 cycles, the specific capacitances of Examples 1-2 and Comparative Example 1 were 63.4, 97.6, and 32.28 F g, respectively. -1 It can be seen that the Co-Zn-NC electrode of Example 2 has the highest specific capacitance. Through the above electrochemical performance test, it can be concluded that the capacitor performance of Example 1-2 is the best.

[0035] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a two-dimensional ultrathin porous carbon nanosheet, characterized in that: include: (1) Zn(NO3)2·6H2O or a mixture of Co(NO3)2·6H2O and Zn(NO3)2·6H2O is mixed with 2-methylimidazole to react to obtain a precursor; (2) After mixing the precursor with a molten salt, annealing the mixture under an inert atmosphere to obtain a two-dimensional ultrathin porous carbon nanosheet, wherein the molten salt comprises a first molten salt and a second molten salt, wherein the first molten salt comprises at least one of KCl and KNO3, and the second molten salt comprises at least one of LiCl, NaCl, ZnCl2, and LiNO3.

2. The method according to claim 1, characterized in that: In step (1), the temperature at which the mixing reaction occurs is room temperature.

3. The method according to claim 1 or 2, characterized in that: In step (1), the ratio of the mass of Zn(NO3)2·6H2O or the total mass of Co(NO3)2·6H2O and Zn(NO3)2·6H2O to the mass of 2-methylimidazole is independently (0.4-0.5):

1.

4. The method according to claim 1 or 2, characterized in that: In step (2), the mass ratio of the precursor to the molten salt is 1:(10-20).

5. The method according to claim 1 or 2, characterized in that: In step (2), the mass ratio of the first molten salt to the second molten salt is (5-8):(2-5).

6. The method according to claim 1 or 2, characterized in that: The annealing temperature is 700°C to 900°C.

7. A two-dimensional ultrathin porous carbon nanosheet, characterized in that: The method is prepared by any one of claims 1 to 6.

8. The two-dimensional ultrathin porous carbon nanosheet according to claim 7, characterized in that: The specific surface area of ​​the two-dimensional ultrathin porous carbon nanosheet is 1200-2500 m 2 / g, preferably 2000~2500m 2 / g, and the pore size of the two-dimensional ultrathin porous carbon nanosheet is 0.5nm~3nm.

9. The two-dimensional ultrathin porous carbon nanosheet according to claim 7 or 8, characterized in that: The thickness of the two-dimensional ultrathin porous carbon nanosheet is 1nm~6nm.

10. A supercapacitor, characterized in that: It comprises the two-dimensional ultrathin porous carbon nanosheet as described in any one of claims 7 to 9.